The Cash Waqfs Debate of 1545-1548: Anatomy of a Legal Debate at the Age of Süleyman the Lawgiver - Hasan Karataş (İnsan & Toplum)
The cash waqfs debate of the mid-sixteenth century is indicative of a very critical phase in the development of the Ottoman legal tradition and scholarly establishment. By bringing the personal stories of the major figures to the fore, this article focuses on the social and political aspect of the debate rather than its intellectual content. As a public legal debate related to a critical social issue the cash waqfs discussion was more than simple scholarly exchange. Behind the points distinguishing different scholarly opinions lined there were sundry social and political groups that struggle for the control of resources. Occasionally personal issues between scholars used to surface in the form of an academic debate. And the outcome of the debate endowed the winning party more than a scholarly prestige. At such a critical juncture in the evolution of the Ottoman scholarly/legal establishment, the winners of this particular legal debate came to be very influential in the formation of the ilmiye. Finally, this debate marked an important turning point in the transformation of the Ottoman ulama from homo academicus to homo politicus.